Strategi Pembelajaran IPA di Masa New Normal : Suatu Studi Kegiatan Belajar Mengajar Siswa - Siti Riva Darwata (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
New Normal is a term to describe human life to coexist with the Covid-19 outbreak, including in learning activities at school. With all the restrictions at this time, the subject of Natural Sciences (IPA) certainly becomes more difficult to implement, because Natural Science is a complex subject that tends to be understood quickly for students. The findings and discussion of this research are presented using a qualitative method through a descriptive approach. Data collection related to the teaching and learning process of students was carried out through a series of in-depth interviews with classroom teachers and students who were considered qualified as subjects and objects of research, which also used the other available documents. The results of the research revealed that in order to adapt the government direction for keeping the community around in a stable health condition, the MTs Kayu Aro School through its policy set two technical solutions related to teaching and learning activities during the new normal period. First, by imposing a narrowing of the range of school activities for a week with the one-day, no-day method. Second, school policy also imposes a reduction in the duration of teaching and learning activities per day. In addition, the school also implements dual process as a learning method, offline and online by utilizing some learning media, such as WhatsApp application or other learning websites.